FRAGMENTED MOTIVES AND POLICIES: THE BELT AND ROAD INITIATIVE IN CHINA - Ye, Min (Journal of East Asian studies, 2021)
Observers have portrayed the Belt and Road Initiative (BRI) variously, as China's great-power strategy, global infrastructure initiative, or commercial projects. Each characterization has had logical reasoning and evidence to support it. But how? How has one initiative been shown to have such varied motives? This article unpacks the Chinese state and establishes that a “tri-block” structure consisting of political leadership, bureaucracy, and economic arms has accounted for such varied motivations and actors in the BRI in China. In the BRI process, the leadership employed strategic rhetoric, and bureaucracies imposed policy ideas. Yet, more pervasively, the implementers have followed commercial motives in specific projects. BRI's strategic rhetoric and hazardous investment have generated external critiques and anti-China backlash, forcing Beijing to readjust the initiative. However, given the tri-block state structure, Beijing's policy adjustment will not be sufficient. Economic actors’ incentives need to be shifted too.